Creating a reading nook for children in conflict with the law at Bahay Pag-asa, Valenzuela City - Ibañez-Padillo, Angelic Grace; Obille, Kathleen Lourdes B.; Santos, Yhna Therese P. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2018)
Internationally, prison libraries are seen as one of the effective ways in shaping the character of inmates and help them transition once again to the outside world; through education and moral upbringing. In the Philippines, there are only a few prison libraries. More so in juvenile centers where children in conflict with the law (CICL) are confined.
This project aimed to provide a library nook for CICL in Bahay Pag-asa, Valenzuela City. Interviews were conducted among the juvenile center staff and surveys were distributed among the CICL. Focus group discussions were also done with the CICL to elicit information needs. After assessing the interviews and surveys, resources to procure were identified in line with its results. Library collection and facilities were bought through sponsorships and donations from various organizations and publishers. The setting up of the library culminated with a ribbon cutting ceremony. The library nook was turned over to Bahay Pag-asa staff through library management briefing. The staff were oriented in library maintenance and sustainability activities such as partnership with organizations, sponsorships, and library advocacy activities. Activities for the CICL such as quiz bees, poetry, poster making contests, role playing activities. There were also other activities that advocated reading, lifelong learning, and application of learned knowledge. The desire of the CICL to learn and read was enticed since the project launch. This project hopes for the children to be prepared and to carry the value of libraries in changing the lives of people as they transition to the outside world.
Special Problem (Master of Library and Information Science)
Keywords: Reading nook -- Bahay Pag-asa -- Valenzuela City